Industry 4.0: Transforming Economy Through Value Added - Topleva, Silviya (Asian Journal of Economic Modelling, 2018)
The article presents the changes that innovations of industrial revolutions have provoked in manufacturing technologies and economic structural and functional relationships. It is concluded that every major industrial revolution (for example, the First and Third Revolutions) was followed by a subsequent technical revolution (respectively, the Second and Fourth Revolutions), which expands the innovation business potential and determines a new pathway for the economic theory development. The deployment of the technological achievements of the Information Revolution provokes the emergence of the digital revolution –Industry 4.0. Due to added value, the digitalization brings out the economic relations into a quality new dimension and transforms economic theory, business models and competitive environment. The high-technological digital environment of the Industry 4.0 achieves simultaneous horizontal and vertical integration and automation of the value chain and value added chain. In the conditions of respecting the requirements of eco-design and clean production, Industry 4.0 involves consumer into the production process and overcomes the scarcity of resources and goods. In this digital high-technological environment, marginal utility theory loses her actuality. The transformations of economic structure and relationships in Industry 4.0 focus on innovations and increase in value added.